The New Media and the Facebook Phenomenon between the Influence and Falsification of Public Awareness - Laadjal, Afifa (Journal of Legal Studies and Researches, 2023)
The research aims to clarify the most common media methods on Facebook. Among the largest sources, he brought in the uses of the types of methods used to falsify the republican awareness, which led to the negative and positive impact on the public, as well as many problems related to respecting ethics and combating media mediocrity that results from clicking on any link and believing any news.